The role of Sá Carneiro in the building of the Portuguese democracy: Memory(ies) of the agents of change through the press - Inácia Rezols, Maria (Historia y Política, 2022)
This article aims to analyse how the press has depicted Francisco Sá Carneiro, founder of the Social Democratic Party, regarding his role in the construction of Portuguese democracy. Debates on the Portuguese transition to democracy focus almost invariably on its revolutionary phase and on the relative importance of its actors and agents of change. Nonetheless, little attention has been paid to the role of civilian leaders during or after the 74-75 Revolution. In addition, the impact of the media on the historical memory of the Portuguese transition remains an underexplored research topic. Considering the importance of the media in shaping public opinion and in the process of building the historical memory, we will undertake a qualitative analysis of piece of news published on Sá Carneiro and his role in Portuguese democratization. Our research will focus on Portuguese and Spanish largest newspapers in order to perceive if Sá Carneiro’s memory also changed abroad. This article argues that the press hasn’t paid much attention to Sá Carneiro’s role in the democratisation process, echoing mythologized visions of the centrist leader.